2020
DOI: 10.1097/qad.0000000000002782
|View full text |Cite
|
Sign up to set email alerts
|

Homonegativity, sexual violence and condom use with women in men who have sex with men and women in West Africa

Abstract: Objective: The study aimed to explore longitudinal interactions between homonegativity and sexual behaviors with female partners among HIV-negative West African men who have sex with men and women (MSMW). Design and method: The community-based cohort CohMSM ANRS 12324 – Expertise France enrolled MSM in Togo, Burkina Faso, Côte d’Ivoire and Mali. Sociobehavioral data were collected every 6 months. Using 30-month follow-up data, a multiprobit analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Implications for HIV epidemics and future research Based on quantitative behavioral indicators and qualitative data, our multilevel synthesis supports the hypothesis that MSMW in SSA may act as a bridging population for HIV transmission in women. Furthermore, it is plausible that the estimated proportions of MSMW in MSM are underestimated here, given that MSMW may be more concealed and thus more challenging to access than exclusive MSM [128]. On the other side, the data presented here are limited to the proportions of MSM engaging in sexual activity and at-risk behaviors with women, which does not necessarily imply that HIV bridging to women occurred.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Implications for HIV epidemics and future research Based on quantitative behavioral indicators and qualitative data, our multilevel synthesis supports the hypothesis that MSMW in SSA may act as a bridging population for HIV transmission in women. Furthermore, it is plausible that the estimated proportions of MSMW in MSM are underestimated here, given that MSMW may be more concealed and thus more challenging to access than exclusive MSM [128]. On the other side, the data presented here are limited to the proportions of MSM engaging in sexual activity and at-risk behaviors with women, which does not necessarily imply that HIV bridging to women occurred.…”
Section: Discussionmentioning
confidence: 83%
“…This probably influences the pressure experienced by MSM to have sex with women. Ongoing work from our systematic review showed that the proportion of selfidentified bisexual MSM, a group with potential overlap with MSMW, was significantly lower in South Africa, compared with other Southern African countries [128].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…21 A previous report from West Africa revealed that inconsistent condom usage with wife/girlfriend was reported in 57% of MSMW. 22 Since MSMW have sex with both genders, there is the possibility that they will transmit HIV and other STIs from a male partner to a female partner or vice versa. 23 Another issue is that MSMW were found to be less likely to have HIV laboratory testing and thus more likely to be unaware of an HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…While these categories are consistent with those adopted in some Northern countries, they will be grouped into broader categories if necessary (such as Employed, Seeking employment, and Other, inactive (Students, Pensioners)) and then considered in relation to educational level. 27 …”
Section: Methods and Analysismentioning
confidence: 99%